(untitled) (Journal of Sciences & Technology, 2021)
The silver nanoparticles are known such as diffusers and efficient light absorbers, because of their strong interactions with visible light through the phenomenon of surface Plasmon resonance (SPR). Local frequency LSPR strongly depends on the size, shape and dielectric medium. The synthesis of silver nanoparticles of different sizes was carried out, using different molar concentrations of silver nitrate at different temperatures in two different solvents (ethanol and methanol). the synthesized nanoparticles were characterized by UV-Visible spectroscopy. The results show the presence of an absorption peak at around 440 nm. A theoretical study based on the use of the simulator COMSOL Multiphysics was developed. It was demonstrated, that the nanoparticles have a spheroids shape and their sizes are of the order of 12 nm. The theoretical results were validated by experimental results.